Increased health threats from land use change caused by anthropogenic activity in an endemic fluorosis and arsenicosis area. (June 2020) - Yuan, Li; Fei, Wang; Jia, Feng; Junping, Lv; Qi, Liu; Fangru, Nan; Xudong, Liu; Lan, Xu; Shulian, Xie
Abstract: Urbanization is conducive to promoting social development and improving living standards. However, the changing land use attributed to urbanization has placed both the environment and humans at risk. Based on the long-term monitoring and the land use change during 2010–2017, we investigated the exposure of fluoride (F) and arsenic (As) in groundwater. We analyzed the temporal and spatial variation of F and As from different land use changes. The study assessed health risk for children by calculating carcinogenic risk and non-carcinogenic risk. Furthermore, we mapped the distribution pattern of F and As using GIS. For the 768 water samples collected from 2010 to 2017, F concentrations ranged between 0.10 and 5.70 mg L −1 (M = 0.68 ± 0.02 mg L −1 ), As concentrations ranged between 0.50 and 71.50 μg L −1 (M = 4.28 ± 0.28 μg L −1 ). A concerning result showed that 6.77% of F concentrations larger than 1.5  mg L −1 and 11.46% of As concentrations larger than 10 μg L −1 based on the recommendation by WHO, respectively. Results proved that land use change caused by human activity increased groundwater pollution and placed human health at risk. High F and As risk were found in southern Taiyuan City. In particular, the groundwater of industrial land suffered from more severe pollution, especially at the frontier of urban and suburban areas in the southern part of Taiyuan City. Land use change attributed to industrial land resulted in major increases in the F and As concentrations in groundwater across 2010–2017. Both carcinogenic risk and non-carcinogenic risk in 2016–2017 were higher than that in 2010–2015. Rational land use planning, strict groundwater protection policies and the regular monitoring of pollution levels are necessary in order to prevent the adverse health of residents. Graphical abstract: Image 1 Highlights: Human activity causes a threat on children's health. Land use change caused by human activity increased fluoride and arsenic concentrations in groundwater. Groundwater under industrial land suffered more serious pollution, especially at the junction of urban and suburban areas. Reasonable land use instruments, groundwater protection policies and regular monitoring are necessary. Abstract : Land use change caused by anthropogenic activity increased fluoride and arsenic concentrations in groundwater. Groundwater under industrial land suffered more serious pollution, especially at the frontier of urban and suburban areas.